The effects of curcumin as dietary supplement for patients with polycystic ovary syndrome: An updated systematic review and meta‐analysis of randomized clinical trials. (13th September 2021) - Abdelazeem, Basel; Abbas, Kirellos Said; Shehata, Joseph; Baral, Nischit; Banour, Sandi; Hassan, Mustafa
Abstract : This review aims to evaluate if there are clinical benefits of curcumin (CUR) in patients with polycystic ovary syndrome (PCOS). Electronic databases (PubMed, EMBASE, Scopus, Web of Science, Cochrane Central, and Google Scholar) were systematically searched to identify only randomized clinical trials (RCTs) that assessed CUR in patients with PCOS from inception to May 5, 2021. Five RCTs were included with a total of 296 patients, with 148 among the CUR groups and 148 patients among the control group. Revised Cochrane risk‐of‐bias tool for randomized trials was used to assess the risk of bias, three RCTs provided a low risk of bias and two provided a high risk of bias. Compared with the control group, CUR was associated with a statistically significant improvement in the glycemic control including fasting blood glucose (MD = −3.67; 95% CI = [−5.25, −2.08], p  < .00001), insulin level (MD = −1.91; 95% CI = [−2.97, −0.84], p  = .0005), homeostasis model assessment of insulin resistance (MD = −0.55; 95% CI = [−0.83, −0.27], p  = .0001), and quantitative insulin sensitivity check index (MD = 0.01; 95% CI = [0.00, 0.02], p  = .0005). The mean difference in total cholesterol was also statistically significant (MD = −15.55; 95% CI = [−30.33, −0.76], p  < .04). The rest of the secondary outcomes, including LDL, HDL, sex hormone, body weight, and CRP, were not statistically significant. This review concluded that among patients with PCOS, the use of CUR demonstrated a significant difference from the control group for glycemic control. Those findings suggest that CUR confers clinical benefits in patients with PCOS. However, due to the limited number of the included studies, further high‐quality studies are needed to establish the clinical efficacy of the CUR.